Analisis Dukungan Keluarga, Status Ekonomi dan Sosial Budaya Terhadap Pernikahan Dini di Desa Sinar Wajo Kabupaten Tanjung Jabung Timur - Lia Artika Sari; Diniyati Diniyati; Enny Susilawati (NHM PRESS, 2021)
Data from the Office of Religious Affairs, Mendahara Ulu District, Tanjung Jabung Timur Regency, through an initial survey, there were marriages of less than 20 years of age, teenagers who married under the age of 19 in 2017 reached 142 out of 1,066 teenagers Early marriage is a problem that can have an impact on the mother, the occurrence of miscarriage in the first child, giving birth to the first child with low birth weight and giving birth with obstructed labor. The background of early marriage is due to economic status, socio-culture and parental support. This research is a qualitative research with in-depth interviews and focus group discussions. This study aims to analyze socio-cultural, family and economic support for early teenage marriage in Sinar Wajo Village, Mendahara Ulu District, Tanjung Jabung Timur Regency in 2019. The method of taking informants is by strata random sampling, the informants in this study were 26 people consisting of 1 village secretary, 1 KUA officer, 6 parents whose children marry early, 6 parents whose children do not marry early, 6 teenagers who marry early and 6 teenagers who do not marry early. The research was conducted from January to June 2019 using research instruments in the form of in-depth interview guidelines and FGD guidelines. The results of the study showed that early teenage marriage in Sinar Wajo Village, Mendahara Ulu District, Tanjung Jabung Timur Regency in 2019, marriage in Sinar Wajo Village was supported by family, socio-cultural and economic status. It is hoped that there will be cooperation between health workers and KUA officers in providing counseling on the dangers of early marriage, including CA. Cervix, giving birth to a low birth weight baby, obstructed labor and easy miscarriage in the first child.